Rate constants of quenching and vibrational relaxation in the OH(A2Σ+, v=0, 1), manifold with various colliders. (14th February 2017) - Martini, L M; Gatti, N; Dilecce, G; Scotoni, M; Tosi, P
Abstract: Laser induced fluorescence is intensively used for the detection of OH in many atmospheric pressure discharge devices. At this pressure, a quantitative knowledge of the collision phenomena in the upper excited state is critical. Here we report the measurement at T   =  300 K of a set of rate constants of electronic quenching and vibrational relaxation of the OH ( A 2 Σ +, v ′ = 0, 1 ) electronic state, by collision with N2, O2, H2 O, CO2, CO, H2, D2, CH4, C2 H2, C2 H4, C2 H6 . These are the main gases in applications like plasma medicine, hydrocarbons reforming and CO2 conversion. Available literature data are revisited, and new data are added, mostly relevant to v ′ = 1 quenching and vibrational relaxation.